2015
DOI: 10.1080/10256016.2015.1013540
|View full text |Cite
|
Sign up to set email alerts
|

Stable hydrogen and carbon isotope ratios of methoxyl groups during plant litter degradation

Abstract: Stable hydrogen and carbon isotope ratios of methoxyl groups (δ(2)Hmethoxyl and δ(13)Cmethoxyl values, respectively) in plant material have been shown to possess characteristic signatures. These isotopic signatures can be used for a variety of applications such as constraining the geographical origin and authenticity of biomaterials. Recently, it has also been suggested that δ(2)Hmethoxyl values of sedimentary organic matter of geological archives might serve as a palaeoclimate/-hydrology proxy. However, depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Their δ 2 H values can be readily measured without isotope fractionation as iodomethane (CH 3 I), which is released upon treatment of the wood with hydroiodic acid . A further advantage is that lignin methoxyl groups of wood are chemically stable and do not isotopically exchange after formation or in the course of biotic and abiotic degradation . Keppler et al compared δ 2 H methoxyl values from trees around the world with corresponding δ 2 H values in meteoric water and found a uniform isotopic fractionation of −216 ± 19‰.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their δ 2 H values can be readily measured without isotope fractionation as iodomethane (CH 3 I), which is released upon treatment of the wood with hydroiodic acid . A further advantage is that lignin methoxyl groups of wood are chemically stable and do not isotopically exchange after formation or in the course of biotic and abiotic degradation . Keppler et al compared δ 2 H methoxyl values from trees around the world with corresponding δ 2 H values in meteoric water and found a uniform isotopic fractionation of −216 ± 19‰.…”
Section: Introductionmentioning
confidence: 99%
“…26 A further advantage is that lignin methoxyl groups of wood are chemically stable and do not isotopically exchange after formation or in the course of biotic and abiotic degradation. 26,27 Keppler et al 25 compared δ 2 H methoxyl values from trees around the world with corresponding δ 2 H values in meteoric water and found a uniform isotopic fractionation of −216 ± 19‰. This value was slightly modified (−213 ± 17‰) by Anhäuser et al 28 Feakins et al 29 applied this method for different tree species in a coastal ecosysthem in Florida and reported that source water δ 2 H values have the greatest influence on δ 2 H methoxyl values.…”
Section: Introductionmentioning
confidence: 99%
“…The results regarding stable carbon isotope analysis might have a substantial impact on the δ 13 C values of plant methoxy groups that have been previously reported . Most of the δ 13 C values of wood methoxy groups that have been measured in the past (~ranging from −20 to −30 mUr) were normalised with CH 3 I reference materials with very negative δ 13 C values (~ −60 to −70 mUr) may need to be corrected by 2–3 mUr towards more negative values.…”
Section: Discussionmentioning
confidence: 95%
“…The precision ('external precision' including IRMS analysis. The precision of the replicate measurements of δ 13 C values obtained by GC/IRMS is ±0.21 mUr and ±0.40 mUr for HUBG1 and HUBG2, respectively.The results regarding stable carbon isotope analysis might have a substantial impact on the δ 13 C values of plant methoxy groups that have been previously reported 7,12,14,19,25,26,35,51. Most of the δ 13 C values of wood methoxy groups that have been measured in the past (~ranging from −20 to −30 mUr) were normalised with CH 3 I reference materials with very negative δ13 C values (~−60 to −70 mUr) may need to be corrected by 2-3 mUr towards more negative values.…”
mentioning
confidence: 85%
“…H.-L. Schmidt has had a most distinguished career in isotope research. It started with the synthesis of radioactive tracer compounds and led to a wide range of fundamental, methodical and applied research on the stable isotope composition of the main elements of the biosphere, principally 13 C/ 12 C, 15 N/ 14 N, 2 H/ 1 H, 18 O/ 16 O and 34 S/ 32 S. That career has been an awe inspiringly long one, 55 years [1] and counting, as is documented by his contribution to a review on the causes and implications of in vivo isotope fractionations [2] in this Special Issue. Young stable isotope researchers may wonder how such a career could have unfolded, what circumstances and coincidences -academic and other -influenced and guided it, and which interactions with colleagues and students accompanied and enriched it.…”
Section: This Special Issue Of Isotopes In Environmental and Health Smentioning
confidence: 99%